Study of Volatility Spillover from Crude Oil Futures to Grain Futures Across Multiple Cycles Based on the EEMD-BEKK-GARCH Model - Xizhao Wang; Mingzhe Pu; Shengxuan Sun; Yu Zhong (Agriculture)
Against the backdrop of increasing financialization of grain markets, the cross-cycle and cross-market contagion among commodities has been intensifying. To investigate the risk spillover among commodities across different cycles, this study selected UK WTI crude oil and soybean, corn, and wheat futures prices from the Chicago Board of Trade as research subjects. Using ensemble empirical mode decomposition (EEMD), the original sequences were decomposed into sub-sequences of different frequencies. Based on these frequency characteristics, long-term, medium-term, and short-term fluctuations were constructed. The BEKK-GARCH model was then applied to explore the volatility spillover across markets under different cycles. The results indicate that in terms of pricing mechanisms, crude oil futures dominate the price fluctuations of grain futures. In terms of risk spillover across different cycles, there is a bidirectional risk spillover effect between crude oil and grain futures in short-term and medium-term fluctuations, while in long-term fluctuations, there is only a unidirectional transmission from crude oil futures to grain futures. Based on the research findings, this paper proposes relevant policy recommendations, aiming to provide government regulatory authorities and futures investors with policy guidance and a theoretical foundation across different cycles.